2013
DOI: 10.1002/jhet.1024
|View full text |Cite
|
Sign up to set email alerts
|

5‐Amido‐ and 5‐Amino‐Substituted Epoxyisoindolo[2,1‐a]tetrahydroquinolines and 10‐Carboxylic Acids: Their Synthesis and Reactivity

Abstract: The interactions between 4‐R‐substituted 2‐furyl‐1,2,3,4‐tetrahydroquinolines (synthesized by the Povarov reaction) and a number of alkenes have been investigated. Maleic, dibromomaleic, dichloromaleic, and citraconic anhydrides, as well as acryloyl, methacryloyl, crotonyl, and cynnamoyl chlorides were used as alkene components. It was shown that the initial N‐acylation of the tetrahydroquinolines was followed by a spontaneous [4+2]‐cycloaddition of an N‐acryloyl substituent to the furan ring. It was establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Our literature search revealed that although tert -enamides have been used as dienophiles for the Povarov reaction to build 1,2,3,4-tetrahydroquinoline blocks [ 25 26 37 ], there were no reports of their usage in the inverse electron demand hetero-Diels–Alder reaction with an N -acyliminium cation. We envisaged that the isoindoloquinoline skeleton synthesized by Kouznetsov et al [ 25 ] and Zaytsev et al [ 26 ] in a 5-step sequence ( Scheme 1 ) could be more conveniently synthesized (3-step sequence, Scheme 1 ) by employing N -aryl-3-hydroxy-isoindolinones as the N -acyliminium ion source and performing [4 + 2] imino-Diels–Alder reactions with tert -enamides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our literature search revealed that although tert -enamides have been used as dienophiles for the Povarov reaction to build 1,2,3,4-tetrahydroquinoline blocks [ 25 26 37 ], there were no reports of their usage in the inverse electron demand hetero-Diels–Alder reaction with an N -acyliminium cation. We envisaged that the isoindoloquinoline skeleton synthesized by Kouznetsov et al [ 25 ] and Zaytsev et al [ 26 ] in a 5-step sequence ( Scheme 1 ) could be more conveniently synthesized (3-step sequence, Scheme 1 ) by employing N -aryl-3-hydroxy-isoindolinones as the N -acyliminium ion source and performing [4 + 2] imino-Diels–Alder reactions with tert -enamides.…”
Section: Resultsmentioning
confidence: 99%
“…Our literature search revealed that although tert -enamides have been used as dienophiles for the Povarov reaction to build 1,2,3,4-tetrahydroquinoline blocks [ 25 26 37 ], there were no reports of their usage in the inverse electron demand hetero-Diels–Alder reaction with an N -acyliminium cation. We envisaged that the isoindoloquinoline skeleton synthesized by Kouznetsov et al [ 25 ] and Zaytsev et al [ 26 ] in a 5-step sequence ( Scheme 1 ) could be more conveniently synthesized (3-step sequence, Scheme 1 ) by employing N -aryl-3-hydroxy-isoindolinones as the N -acyliminium ion source and performing [4 + 2] imino-Diels–Alder reactions with tert -enamides. Our literature search also infuses confidence in the proposed scheme because the synthesis of N -aryl-3-hydroxyisoindolinones is well studied and standardized [ 13 – 15 ] and the reactions analogous to the final step of imino [4 + 2] Diels–Alder reactions between N -acyliminium ions and electron-rich dienophiles are reported [ 13 – 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade our synthetic group has published some effective strategies for the synthesis of 3,6a-epoxyisoindoles annulated with various heterocycles (Zubkov et al 2010(Zubkov et al , 2011(Zubkov et al , 2014Zaytsev, Mikhailova et al 2012;Zaytsev et al 2013). These strategies were based on the intramolecular cycloaddition reaction of α,βunsaturated acid anhydrides to the heterocycles containing an α-furfurylamine fragment (IMDAF reaction) (Vogel et al, 1999;Zubkov et al, 2005).…”
Section: S1 Structural Commentarymentioning
confidence: 99%
“…For reviews on intramolecular cycloaddition reactions of ,-unsaturated acid anhydrides to furfurylamines (IMDAF reactions), see: Vogel et al (1999); Zubkov et al (2005). For related compounds, see: Zubkov et al (2009Zubkov et al ( , 2014; Zubkov, Galeev et al (2010); Zubkov, Zaitsev et al (2010); Zaytsev et al (2012Zaytsev et al ( , 2013; Toze et al (2011 Table 1 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%